Investigation on the Physical Properties of Varistors According to Temperature - Ahran Min; Sin-Dong Kang; Jae-Ho Kim (IEEE Access, 2022)
This study aims to determine the basic physical properties of varistor, which is a protective element in a surge protection device (SPD) used to prevent damage to electric and electronic equipment due to lightning. To do this, we conducted tests of insulation resistance, leakage current, heating characteristics, accelerated aging, impulse current, and operating duty according to temperature. To measure insulation resistance and leakage current, an S1-1568 insulation resistance tester was used. To measure the temperature rise according to a change in the external environment, a convection oven was employed. For the impulse current test, a surge current generator of a direct lightning strike, which was designed and manufactured according to the IEEE and UL standards, was used. We verified that the leakage current increased and the insulation resistance decreased as the voltage and outside temperature were applied to the varistor. This meant that heating and deterioration accelerated due to the leakage current, depending on the place where the SPD was applied. Heat accumulation due to constant heating could cause a change in the physical properties of a varistor and degradation of performance, leading to failure. The impulse current test results of the varistor through the operating duty test showed that changes in insulation resistance and leakage current did not occur significantly with an increase in the number of impulse applications when the less than the maximum surge currents. On the other hand, the maximum surge current was exceeded, the insulation resistance rapidly decreased, which also rapidly increased the leakage current.